OVERVIEW OF THE SEVERITY LEVEL AND RISK FACTORS FOR ANEMIA IN WOMEN IN INDONESIA - Elvia Gusti; Ummi Kalsum; Silvia Mawarti Perdana (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Anemia remains a significant public health problem, especially among women of reproductive age (WRA), as it affects maternal and infant health and increases the risk of pregnancy complications. The prevalence of anemia among WRA in Indonesia is still relatively high. Objective: This study aimed to describe the severity of anemia and its risk factors among WRA in Indonesia in 2023. This study used a descriptive quantitative approach with a cross-sectional design based on secondary data from the 2023 Indonesian Health Survey (SKI). The population included all WRA (15–49 years) in the biomedical sample. Data were analyzed using univariate analysis to obtain frequency and percentage distributions. Anemia among WRA was still observed with varying levels of severity. Most respondents were aged 20–35 years, had completed senior high school, were unemployed, had parity <2, no history of abortion or infectious disease, were not chronically energy deficient, had good access to health services, and were in the upper-middle socioeconomic group. Conclusion: Anemia among WRA in Indonesia remains a concern, requiring targeted prevention and intervention efforts.